Criticism, mediation, and new spatialities: An STS and STG Approach - Argyriou, Konstantinos (Eikón / Imago, 2019)
Throughout the last few decades, technological advances have transformed the museum experience, questioning various related practices, such as art criticism and cultural mediation, which are seen both confronted with each other and affected by the proliferation of narratives and opinion agents. Such democratization has raised the problem of how to legitimize discourses, make use of bodies, senses and desires, and facilitate change in the interior and exterior of contemporary art museums. The present reflection aspires to conceptualize the notion of the intermediate as an axis for the discussion on these topics. Moreover, we perform an epistemological itinerary drawing from interdisciplinarity and STG studies, in order to explore how biases and inhibitory forces inside institutions hinder the process of inhabiting intermediate spaces, whereas alternative approaches, hybrid and situated, foster intersubjectivity, exchange and active implication.